Trends in EU consumers' attitude towards fresh-cut fruit and vegetables. (July 2017) - Baselice, Antonio; Colantuoni, Francesca; Lass, Daniel A.; Nardone, Gianluca; Stasi, Antonio
Highlights: Consumers of EU countries show similar preferences towards fresh-cut products. Market split into two segments with opposite preferences towards fresh-cut products. Income is an important segmentation variable in EU fresh-cut market. Food safety innovations are perceived better than those regarding convenience. Fresh-cut F&V consumers show high WTP for natural preservatives and quality information signal. Abstract: Although there is a long-term decrease in the consumption of fruits and vegetables (hereafter F&V), fresh-cut products, because of their convenience, represent a valid alternative to counteract this negative trend. In fact, the fresh-cut sector is showing positive figures, and innovation in product quality and safety attributes, which are generally valued by consumers. Nonetheless, which product innovations will effectively take place in the coming years? Will they be accepted by consumers? Will they increase the probability of switching from fresh to fresh-cut F&V? Our study, with the help of on-field research, aims at analysing the trending attributes in the fresh-cut F&V industry, and evaluating their impact on segments of F&V consumers' preferences in terms of attitude and willingness to pay. Therefore, we applied a latent class discrete choice model with an original dataset consisting of face-to-face interviews conducted across EU. Results of the study highlight the similarities in preferences of consumers across the EU countries and the relevance of shelf-life and food safety attributes in orienting choices.